Nursing Code of Ethics Practice and Associated Factors Among Nurses Working in Ethiopia: A Cross-Sectional Study - Mulugeta Hailu Tolosa MSc; Daniel Mengistu Bekele PhD; Addisu Dabi Wake MSc (SAGE Publishing, 2024)
Background Codes of ethics provide essential guidance for nursing like those of other professions. This is because nurses are increasingly challenged by complex concerns in their practice. Ethical practice is the foundation for nurses because they deal with ethical issues on daily basis. Objectives This study was aimed to determine the nursing codes of ethics practice and associated factors among nurses working in selected public hospitals in Addis Ababa, Ethiopia. Methods Institution-based cross-sectional study was conducted in selected public hospitals in Addis Ababa between mid-March and June 2022. Study participants were selected using a simple random sampling technique. Result Of the 367 nurses, 334(91%) were aged ≤35 years. The majority 221(60.2%) of nurses were married. The level of a good "nursing code of ethics" practice among nurses was 48.8%. Having training on nursing ethics/code of ethics after school [AOR = 2.41, 95%CI: 1.24, 4.68, p -value = 0.009], good job satisfaction [AOR = 1.58, 95%CI: 1.25, 7.35, p -value = 0.022], good knowledge towards "nursing code of ethics" [AOR = 3.11, 95%CI: 1.59, 6.05, p -value = 0.001], and positive attitude towards "nursing code of ethics" [AOR = 8.56, 3.81, 18.25, p -value = 0.000] were factors significantly associated with "nursing code of ethics" practice. Conclusion The level of good "nursing code of ethics" practice among nurses was relatively low. Training in nursing ethics/code of ethics after school, job satisfaction, knowledge about "nursing code of ethics", and attitude towards "nursing code of ethics" were factors significantly associated with "nursing code of ethics" practice. Health education and training on "nursing codes of ethics" need to be provided to improve nursing codes of ethics practice among nurses.